Mechanical bending strength of (Bi0.5Na0.5) TiO3-based lead-Free piezoelectric ceramics. Issue 3 (1st September 2017) - Takahashi, Hiroaki; Nagata, Hajime; Takenaka, Tadashi
Abstract: (Bi0.5 Na0.5 )TiO3 [BNT] is expected as one of candidate lead-free materials because these ceramics show relatively good high-power piezoelectric properties. In this study, we tried to understand the bending strength and fracture behavior of the BNT-based ceramics. To measure the bending strength, a three-point bending test on the basis of JIS was conducted using 12.0 × 4.0 × 1.0 mm 3 specimens. An average bending strength, σ A, of pure BNT ceramics sintered at 1100 °C for 2, 12 and 24 h were 217, 195 and 187 MPa, respectively. It is cleared that the σ A increased with decreasing the sintering time, (grain size and pore size). We also investigated the bending strength of Nb2 O5 doped BNT ceramics [BNT-Nb x, x  = 0.05 ∼ 1.5 wt%] and MnCO3 doped BNT ceramics [BNT-Mn x, x  = 0.5 and 1.0 wt%]. Values of the σ A of BNT-Nb 0.5 and BNT-Mn 0.5 were 222, and 188 MPa, respectively. It is clarified that soft dopants (Nb) can improve the bending strength of BNT-based ceramics. Additionally, hot-pressed BNT [HP-BNT] were sintered at 1050 °C for 5 h, and the σ A of HP-BNT was 245 MPa.